RETRACTED: Branda et al. Zoonotic Paramyxoviruses: Evolution, Ecology, and Public Health Strategies in a Changing World. Viruses 2024, 16, 1688 - Francesco Branda; Grazia Pavia; Alessandra Ciccozzi; Angela Quirino; Nadia Marascio; Giovanni Matera; Chiara Romano; Chiara Locci; Ilenia Azzena; Noemi Pascale; Daria Sanna; Marco Casu; et al. (Viruses)
The journal retracts the article “Zoonotic Paramyxoviruses: Evolution, Ecology, and Public Health Strategies in a Changing World” [...]